Nocturnal Vaginal pH Monitoring: A Possible New Assessment Method for Female Sexual Function - Mehmet Reşit Gören; Cevahir Özer; İbrahim Oğuzülgen (Journal of Urological Surgery, 2023)

(untitled)
Objective:The aim of this preliminary study was to investigate whether women have nocturnal vasocongestion episodes like men and whether nocturnal vaginal pH (NVpH) monitoring can be used for female sexual function assessment-like nocturnal penile tumescence and rigidity (NPTR) test in men.Materials and Methods:Twelve premenopausal volunteers were included in the study. All women were within sexually active age and had normal hormonal profiles. NVpH was performed in an ambulatory manner on the same day and phase of the menstrual cycle. Female sexual function index (FSFI) scores, lubrication scores, and clitoral artery peak systolic velocity (PSV) were recorded. The volunteers were grouped according to the number of elevated pH episodes (EPE).Results:Four women had four or more EPEs and constituted group 1. Eight women had 3 or less EPEs and constituted group 2. Group 2 had statistically significantly lower FSFI scores and clitoral artery PSV (p=0.001 and p=0.014, respectively). However, there was no statistically significant difference between the groups for lubrication scores and age.Conclusion:The results of this preliminary study suggested that women and men has the same nocturnal vasocongestion episodes and NVpH measurement in women might be considered as analogous to NPTR in men.